Bridging Law and Practice in Natural Resource Governance: A Narrative Review - Hermansyah (Legalis : Journal of Law Review, 2024)
Legal frameworks for natural resource governance play a critical role in determining equitable access, sustainable use, and environmental protection. This study aims to synthesize current research on legal structures governing natural resources, with a particular focus on marginalized communities in developing countries. A narrative review approach was employed, utilizing scholarly databases such as Scopus and Google Scholar. Boolean keyword combinations including "legal framework," "natural resource governance," and "sustainability" guided the literature search, while inclusion and exclusion criteria ensured relevance and rigor. Findings show that legal systems vary widely across jurisdictions, yet common patterns emerge: insufficient public participation, weak enforcement, and fragmented regulations often limit the effectiveness of natural resource laws. Case studies from Brazil, Bangladesh, Ghana, and Thailand illustrate the disconnect between policy intent and implementation, especially in protecting the rights of indigenous and local communities. Moreover, legal ambiguity and institutional weaknesses contribute to conflict over land and water resources. Discussion reveals that systemic issues—corruption, limited institutional capacity, and political inertia—continue to undermine the legal empowerment of marginalized stakeholders. To address these challenges, the review suggests policy reforms emphasizing participatory governance, community-based resource management, and integration of local knowledge. Ultimately, bridging the gap between theory and practice in legal resource governance requires both international cooperation and local legal innovation to achieve sustainability and justice.